Determining training needs and their impact on evaluating the performance of workers in sports facilities (A field study conducted on the workers of the multi-sports complex office in the wilaya of Laghouat) - BENZIANE , Tahar; TAFIROULT , Billal (Social Empowerment Journal, 2021)
This study aims to determine the training needs and their impact on evaluating the performance of workers in the sports facilities by determining the extent to which scientific methods are used in determining the training needs of workers in the sports facility and to identify the standards adopted in determining training needs. Therefore, among the most important results of this study was the discovery of the extent The limitations of the performance appraisal system within the facility through its reliance on the observations and reports of the serum heads and the interference of personal factors in the performance evaluation process, as well as the establishment’s management’s reliance on a single standard for evaluating performance, which is the effectiveness point. The training courses provided by the management of the facility are aimed at promotion.